Aplikasi Virtual Reality 3 Dimensi Sebagai Media Promosi Waterboom XYZ - Mamay Syani; Muhammad Taufik Faturrahman; Firdaus Laia (Jurnal Informatika, 2023)
Currently, the tourism sector is one of the sectors affected in terms of income caused by the COVID-19 pandemic, one of the things that can help the tourism sector at this time is, with information media carried out to promote the tourism sector. To overcome the problems above, tools are needed to help the process mentioned above, and the tool recommended by the author is to make an Android-based virtual reality application, so it is hoped that by using the virtual reality application, people will become more interested because they can feel the situation around them. which is similar to the real situation before visiting a tourist place. In this study the authors took a case study in one of the tourism places in Banten, especially in Lebak Regency, namely Waterboom XYZ. In the development of this virtual reality application, the method used is the Multimedia Development Life Cycle (MDLC) and the tools used in the development of this virtual reality application use the C# programming language provided in Unity 3D and the Blender application in making 3D modeling. From the test results on the system that has been built, it is found that the system has had a performance that is in accordance with the user's needs along with the results of the User Acceptance Test which received a positive response with a percentage of 82.80%.